(untitled) (American Journal of Islam and Society, 1999)
Professor Mushtaqur Rahman, a renowned Muslim geographer, who was born on July 1,1933 in Agra (India), died of cardiac arrest at Des Moines, Iowa (USA), on November 5, 1999. He had heart problems for several years that had slowed down his academic and social service activities but never deterred him from performing them. In 1947, he migrated to Pakistan, a country he loved dearly and lived to serve throughout his life. Still, his contributions went beyond it in a number of ways. Having done his B.A. (1953) and M.A. (1955) from the University of Karachi, he taught at Islamiah College, Karachi, and Sindh University, Hyderabad for a few years. He earned his Ph.D. degree in Cultural Geography, from Louisiana State University in 1960, and did postdoctoral research at the University of Geisen, Germany in 1966-67. He served in the Department of Geography, University of Karachi, Pakistan from 1963 to 1969. He was appointed Professor of Geography in the Department of Anthropology, Iowa State University (ISU), Ames, Iowa. He served ISU till his retirement in May 1998. Dr.. Rahman’s contribution to the field of Cultural Geography of South Asia has been recognized worldwide. In Professor Rahman was combined an activist and quiet researcher. He was a founding member of the Old Students’ Association of Karachi University (OSAKU), which he served in various capacities. Besides carrying out advisory duties for the Muslim Students Association at ISU, he organized for its students and faculty many study tours of Pakistan and brought a number of Pakistani scholars to Iowa State. His main scholarly contributions are through his very long, sincere, dedicated service to the Association of Muslim Social Scientists (AMSS) and through his many worthy publications in the field of political and cultural geography. Not only did he serve AMSS as its vice president with one of its founders, Dr. AbdulHamid AbuSulayman, but he was also elected its ...